Relationship between sexual function and quality of life in obese persons seeking weight reduction. (31st May 2013) - Moore, Reneé H.; Sarwer, David B.; Lavenberg, Jeffrey A.; Lane, Ilana B.; Evans, Joanna L.; Volger, Sheri; Wadden, Thomas A.
<x xml:space="preserve">Abstract</x> Objective This study investigated sexual functioning in persons with obesity and seeking weight loss, and the associations of sexual functioning with relevant demographic and clinical variables as well as quality of life were investigated. Design and Methods Participants were enrolled in a two‐year randomized clinical trial. Participants were obese and had at least two components of metabolic syndrome. Male and female sexual functioning was assessed by the International Index of Erectile Function (IIEF) and the Female Sexual Function Index (FSFI) respectively. Results The rate of female sexual dysfunction was 29%. The rate of erectile dysfunction (ED) was 45%. Of the characteristics considered, FSD was associated with age (P = 0.002). ED was significantly associated with age and physical functioning (both P < 0.01). Conclusions A large minority of patients with obesity reported sexual dysfunction. The occurrence of sexual dysfunction was associated with age, but, surprisingly, not weight‐related comorbidities. This may be the result of the nature of the study sample or the methods used to administer the questionnaires that assessed sexual functioning.